2009
DOI: 10.1016/j.ultsonch.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted oxidative process for sulfur removal from petroleum product feedstock

Abstract: A procedure using ultrasonic irradiation is proposed for sulfur removal of a petroleum product feedstock. The procedure involves the combination of a peroxyacid and ultrasound-assisted treatment in order to comply with the required sulfur content recommended by the current regulations for fuels. The ultrasound-assisted oxidative desulfurization (UAOD) process was applied to a petroleum product feedstock using dibenzothiophene as a model sulfur compound. The influence of ultrasonic irradiation time, oxidizing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…The effects of extraction process parameters (temperature, solvent/oil ratio and mixing speed) has been previously investigated 11 and the results showed that the solvent/oil ratio had the greatest effect on extraction efficiency, which also confirms the literature data 13,14 . The results presented in Fig.…”
Section: Extractionsupporting
confidence: 80%
“…The effects of extraction process parameters (temperature, solvent/oil ratio and mixing speed) has been previously investigated 11 and the results showed that the solvent/oil ratio had the greatest effect on extraction efficiency, which also confirms the literature data 13,14 . The results presented in Fig.…”
Section: Extractionsupporting
confidence: 80%
“…In a similar study, treatment using application of ultrasonic energy (20 kHz) in aqueous and mixed alkali media (1:1 KOH and NaOH) on coals collected from Assam and Nagaland, India showed that the maximum removal of ash, pyritic sulfur, sulphate sulfur and total sulfur were 87.52 %, 83.92 %, 12.50 % and 18.80 %, respectively (Saikia et al 2014c). Ultrasound assisted coal de-sulfurization and de-ashing is partially green approach that has been recently studied by other researchers (Hoffmann et al 1996;Ze et al 2007;Wang and Yang, 2007;Mello et al 2009;Shen et al 2012).…”
Section: Coal Distribution and Its Characteristics In Northeast Indiamentioning
confidence: 99%
“…For H 2 O 2 volumes higher than 0.25 mL, no significant improvement was observed (ANOVA, p b 0.05) and nitrogen removal did not exceed 97%. In spite of quinoline being extracted by acetic acid and methanol not requiring the use of H 2 O 2 , it is still necessary to achieve better ODS efficiency, as shown in previous works [32,34,44]. In addition, it can contribute to oxidize other nitrogen compounds which are not soluble in solvent phase and have to be converted to N-oxidized compounds before the extraction from oil.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…The feasibility of combining oxidizing conditions and US energy for sulfur removal has been proposed in some works [32][33][34][35][36]. However, in a similar way to conventional hydrodesulfurization process, the presence of nitrogen compounds decreases the efficiency of sulfur removal, and most of works do not evaluate the efficiency of ultrasoundassisted ODN, or even the effect of nitrogen in ODS processes.…”
Section: Introductionmentioning
confidence: 99%